Mapping Potential Habitat Characteristics and Identification of Migratory Raptor Species in the Sabang City - Dhea Rhamadini; Aida Fithri; Wira Dharma; Heri Tarmizi (Postgraduate, University of Mataram, 2025)
This study aims to identify raptor species, map ideal habitat characteristics, and estimate potential habitat areas in Sabang City. The method includes field exploration to collect data on raptor species and spatial analysis using ArcMap 10.8 and Google Earth Engine to download environmental variable data. This study found seven identified species namely: Pernis ptilorhynchus, Accipiter soloensis, Accipiter gularis, Butastur indicus, Halieentus leucogaster, Ichtyophaga ichtyaetus, and Falco peregrinus where five species are migratory and two species are residential. Ideal habitat characteristics include surface temperature of 26–30 °C, NDVI values between 0.43 and 1.00, land slope of 0–2 %, 0–200 m above sea level, and rainfall of 1.500–2.000 mm/year. The total area of potential habitat identified was 674 hectares or 5.51% of the total area of Sabang City. These findings can support sustainable habitat management and raptor conservation, and provide valuable information on management policies to protect migratory birds in the area.